A Philosophical Examination of Social Justice and Child Poverty - Schweiger, Gottfried (Springer Nature, 2015)
This book examines child poverty as a topic of social justice. The authors develop a theory of social justice for children based within the capability approach, apply it to the injustice of child poverty and propose a theory of the responsibilities of different agents towards children living in poverty.